The materiality of reading - Schilhab, Theresa; Walker, Sue, 1954- (Aarhus University Press, 2020)
We read e-books and printed books. But are there differences in how and where we read? And what opportunities does a digital reading environment bring for writers and designers? 'The materiality of reading' explores the experience of reading by examining the interaction between the reader and the object of reading. Bringing together an array of disciplinary perspectives such as neurobiology, embodied reading and typography, we aim to understand how the materiality of the text enhances reader engagement with digital and physical books. The papers of this anthology are the result of academic discussions and empirical explorations at universities in Zadar, Vilnius, Reading and Stavanger as the authors are all members of the European research initiative, "Evolution of Reading in the Age of Digitisation."